PERSEPSI DAN STRATEGI SEKTOR PERTANIAN DALAM MENGHADAPI RISIKO PERUBAHAN IKLIM : STUDI KOMPARASI PULAU ARANG (BANGLADESH) DAN SEMARANG (INDONESIA) - Eva Nurrahmi Lukman; Mangapul Parlindungan Tambunan; Raldi Hendro Toro Seputro Koestoer (Jurnal Environmental Science, 2021)
ABSTRACTClimate change is a serious environmental problem that cannot be avoided due to global warming. This is because the impacts of climate change have been felt in every aspect of human life, one of which is the agricultural sector. Agriculture is the sector that is experiencing the most serious impact due to climate change because the agricultural sector relies on the water and weather cycle to maintain its productivity. Humans alone cannot control climate behavior. Arang Island in Bangladesh and Semarang district, Indonesia are faced with the threat of climate change risks in agriculture. The purpose of this paper is to review and compare the risks of climate change in the two regions with descriptive methods and to examine how the strategies of the two regions in dealing with climate change. The analysis shows that the people of the charcoal islands in Bangladesh applied several adaptation strategies in agriculture such as implementing new or alternative agricultural practices, changing planting times, and cultivating short-duration varieties. And farmers in Semarang district can change cropping patterns or shift planting times according to the arrival of the rainy season to reduce the risk of crop failure.